VISUAL ANALYSIS OF CIRENDEU BATIK MOTIFS - Damayanti, Anandhita Alvina; Falah, Asep Miftahul (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
This research is based on the emergence of Cimahi Batik as an identity of the city in the context of its 8th anniversary, which took place on June 21, 2009. The culture and natural resources of the town of Cimahi inspofCimahi batik. One of the motifs that characterize Cimahi batik is the Cirendeu motif. The inhabitants of the traditional village of Cirendeu are known to consume cassava and Sunda Wiwitan beliefs. So far, the development of Cirendeu batik motifs has been inspired only by culture and natural sources of inspiration, especially as inspiration for batik motifs and colors. The research uses qualitative methods because the object of the study is to understand and interpret the meaning of Cirendeu batik motifs, which aim to develop the concept of sensitivity to discuss the problems encountered, explain the reality related to the pursuit of theory from below, and create an understanding of the phenomena experienced. This study also uses Edmund Burke Feldman’s theoretical approach to art criticism. In this theory, four phases are known in the analysis of the work: description, formal analysis, interpretation, and evaluation. The results of this research are the reappraisal and development of one of the identities of Cimahi, namely batik, the reappraisal and development of Cireundeu batik motifs, which have outstanding natural and cultural potential, and the uncovering of the symbolic meanings of color signs and symbols, which are the characteristics of Cimahi batik. Keywords: Motifs, Cimahi, Batik Cirendeu.